Review ongoing research of several countries on the interference between FSS and BWA - Abdulrazak, Lway Faisal (Int Assoc Engineers-Iaeng, 2008)
The purpose of this paper is to provide a general overview of previous and current communications governments and intergovernmental bodies around the world. They have been increasingly reporting incidents where fixed satellite services (FSS) are being disrupted by interference from terrestrial wireless services in the extended and standard C-band frequencies (3.4 to 4.2 GHz). However, comparisons, analysis and conclusions are included into this paper to provide the upcoming researchers with the best extracts. Furthermore, it gives an idea regarding how different countries can have different consequences based on different issues. Finally, realization the impact of forthcoming technology on satellite used under the C-band category have been discussed in the conclusions.